Elizabeth Crosby: Titan of Neuroanatomy and Friend of Neurosurgery. Issue 2 (February 2022) - Saleh, Sara; Holste, Katherine; Chan, Alvin; Muhlestein, Whitney; Hsu, Frank; Muraszko, Karin
Abstract : Elizabeth Crosby (1888-1983) is a beloved and well-respected titan of neuroanatomy. Her contributions to our understanding of neuroanatomy are rooted in her seminal text, The Comparative Anatomy of the Nervous System of Vertebrates, Including Man, published in 1936, which is a masterful and comprehensive account of comparative neuroanatomy. Her later texts, Correlative Neurosurgery and Correlative Anatomy of the Nervous System, are standard reference texts to this day. Her mentorship of graduate students, close work with the University of Michigan neurosurgery department, and the quality of her research and scientific publications were recognized with many awards, culminating in the National Medal of Science presented by President Carter in 1980.